Effect of topiramate on sweat chloride level while screening for cystic fibrosis. (5th September 2018) - Siddaiah, Roopa; Thau, Eve; Graff, Gavin
Abstract : Cystic fibrosis is the most common life-limiting genetic condition in Caucasians caused by Cystic Fibrosis Transmembrane conductance Regulator (CFTR) gene mutations. Sweat chloride is the current gold standard for diagnosis where values >60 mmol/L are diagnostic and values >30 mmol/L are indeterminate. There is limited literature on the effect of medications on the sweat chloride values. We report a case of topiramate being responsible for false-positive testing which resulted in overutilisation of medical resources and psychosocial stress on the family. Topiramate should be considered during the interpretation of the gold standard testing as one of the cause of false-positive sweat tests.